Contemporary issues in building collapse and its implications for sustainable development - Windapo AO; Rotimi JO (http://www.mdpi.com/journal/buildings/, 2012)
This paper examines contemporary issues in building collapse and its implications for sustainable development in Nigeria. It explores whether the approach to construction by industry stakeholders is in line with the principles of sustainable development following the spate of building collapses in Nigeria. The rationale for the investigation stems from the view by scholars that construction industry stakeholders' do not seem to consider the future in their current activities. The study establishes that the approach to construction by industry stakeholders do not match sustainable principles, and contributes to general under perforxmance of buildings. The paper recommends an overhaul of planning and implementation policies for building development regulations (e.g., building codes). The Nigerian government, as a major construction stakeholder should initiate sustainable construction measures and enforce this as best practice for the construction industry.
Keywords: Building collapse; Construction industry; Economic growth; Ethics; Sustainability; 1201 Architecture; 1202 Building; 1203 Design Practice and Management